متطلبات تفعيل المعامل الافتراضية في مدارس المرحلة الثانوية من وجهة نظر معلمات الفيزياء بمدينة الرياض - الزيادي، مها بنت مشعان بن محمد; الشويعر، عبير بنت صالح بن عبدالعزيز (مؤسسة التربية الخاصة والتأهيل التربوي, 2024)
هدفت الدراسة إلى التعرف على المتطلبات المادية والبشرية لتفعيل المعامل الافتراضية في مدارس المرحلة الثانوية من وجهة نظر معلمات الفيزياء بمدينة الرياض، وكذلك الكشف عن معوقات تفعيل المعامل الافتراضية في المدارس الثانوية، واعتمدت الدراسة على المنهج الوصفي المسحي، واتخذت الاستبانة أداة لها في جمع المعلومات والبيانات، وتكون المجتمع من جميع معلمات الفيزياء في المدارس الحكومية في مدينة الرياض والبالغ عددهن (٥٨٧) معلمة، حيث تشكلت عينة الدراسة من (۲۲۰) معلمة وتم اختيارهن بالطريقة العشوائية، وكانت من أبرز نتائج الدراسة: 1- أن معلمات الفيزياء (موافقات بشدة) على المتطلبات المادية لتفعيل المعامل الافتراضية، والتي كان من أبرزها: توفير شبكة إنترنت في المدرسة وجهاز حاسب آلي شخصي لمعلمات الفيزياء، وتصميم برامج المحاكاة الافتراضية بشكل مشوق وجذاب. 2- أن معلمات الفيزياء (موافقات بشدة) على المتطلبات البشرية لتفعيل المعامل الافتراضية والتي كان من أبرزها: تخفيف الأعباء المكلفة بها معلمة الفيزياء، وتوفر فريق للدعم الفني مؤهل ومدرب لتجهيز برامج المعامل الافتراضية وتحفيز الطالبات لاستخدام المعامل الافتراضية والتفاعل معها. 3- أن معلمات الفيزياء (موافقات بشدة) على معوقات تفعيل المعامل الافتراضية، والتي كان من أبرزها: قلة عدد أجهزة الحاسب الآلي بما لا يفي باحتياجات الطالبات، ضعف شبكات الاتصال والإنترنت في المدرسة وضعف الدعم الفني للمعامل الافتراضية في المدرسة لصيانة ومتابعة المعامل الافتراضية. The study aimed to identify the physical and human requirements for activating virtual laboratories in high schools from the point of view of physics teachers in Riyadh, as well as revealing obstacles to activating virtual laboratories in high schools. The study depended on the descriptive survey method, and the questionnaire was used as a tool for collecting information and data. The community consisted of the (587) female physics teachers in governmental schools in the city of Riyadh. The study sample consisted of (240) female teachers, and they were chosen randomly. The most prominent results of the study were: 1- Physics teachers (strongly agree) on the material requirements for activating the virtual laboratories, the most prominent of which were: providing an internet network in the school and a personal computer for physics teachers, and designing virtual simulation programs in an interesting and attractive way. 2- Physics teachers (strongly agree) with the human requirements for activating the virtual laboratories, the most prominent of which were: reducing the burdens assigned to the physics teacher, providing a qualified and trained technical support team to prepare the virtual laboratories programs, and motivating students to use the virtual laboratories and interact with them. 3- Physics teachers (strongly agree) with the obstacles to activating the virtual laboratories, the most prominent of which were: the small number of computers that do not meet the needs of students, poor communication networks and the Internet in the school, and weak technical support for the virtual laboratories in the school to maintain and follow up the virtual laboratories.
Keywords: التعليم الإلكتروني -- تعليم الفيزياء -- المعامل الافتراضية